Bay‘ Mumtalakāt al-Waqf: Dirāsah Taḥliliyyah fī Ḍau’ Tashrī‘āt al-Waqf fī Hukumah Māliziyā - Muhamad Firdaus Ab Rahman; Hussein ‘Azeemi Abdullah Thaidi; Mohammad Naqib Hamdan; Siti Farahiyah Ab Rahim (Universitas Islam Negeri Jakarta, 2022)
This article aims to critically examine the issue of selling waqf properties in Malaysia's waqf legislations. This tudy adopts a qualitative methodology employing field work data. The findings indicate that even though the waqf fiqh provides a choice of periods to be either temporary or permanent waqf, the Malaysian Waqf laws adopt permanent waqf and prohibits the temporary waqf for the sake of public interest (maslahah). Therefore, waqf properties cannot be cancelled by a donor, and that waqf land cannot be sold, given as a present, or bequeathed. The finding established that the Waqf laws are consistent with the waqf's aims. Thus, this paper proposes that each State's Waqf Corporation and Islamic Religious Council in Malaysia needs to conduct a review of the existing waqf rulings and legal framework to ensure that they are consistent with the waqf purpose for benefiting donors, waqf holdings, and beneficiaries.Keywords: sell; Waqf; Property; legislation; Malaysia ملخ: تهدف هذه الورقة إلى دراسة المواد القانونية الشرعية المتعلقة ببيع ممتلكات الوقف في دولة ماليزيا. وتعتمد هذه الدراسة على المنهج النوعي مع استخدام المناهج الاستقرائية والوصفية والمقارنة والميدانية في تحليل البيانات. ومن أهم نتائج هذه الورقة أن تشريعات الوقف لدولة ماليزيا لا تجيز الوقف المؤقت وانتهاء الوقف ورجوعه وبيعه، وهذا دليل على أن تشريعات الوقف في دولة ماليزيا تتفق مع مقاصد الوقف أنه لا يباع أصلها ولا يوهب ولا يورث، ويكون الوقف مستمرا غير مقطوع. وتقترح هذه الورقة تشجيع هيئات الأوقاف لكل ولاية في ماليزيا على تقويم المواد القانونية المنصوصة في قانون الوقف الحالي حتى تتفق مع مقاصد الوقف لمصلحة الواقفين والموقوف عليهم والأموال الموقوفة. .يازيلام؛ فقو ؛نوناق ؛تاكلتمم ؛عيب :ةيحاتفلما تاملكلا